2012
DOI: 10.1002/ptr.4662
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide B Reduces Neuronal Cell Apoptosis in the Traumatic Rat Brain: Possible Involvement of Toll‐like Receptor 4 and Nuclear Factor Kappa B Pathway

Abstract: Ginkgolide B (GB) has been demonstrated to have a variety of pharmacological actions. Accumulating evidence indicates that GB may exert a protective effect on brain injury. The study was designed to investigate the influence of GB on toll-like receptor 4 (TLR-4) and nuclear factor κB (NF-κB)-dependent inflammatory responses and neuronal cell apoptosis after traumatic brain injury (TBI). Wistar rats were subjected to 5, 10 and 20 mg/kg GB daily for 5 days, intraperitoneally, following TBI. Rats were sacrificed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…For example, oxymatrine, which has anti-inflammatory, antioxidative, and antiapoptotic activities, suppresses TLR4 and NF-κB gene expression and decreases production of proinflammatory cytokines, such as IL-6, TNF-α, and IL-1β [104]. Ginkgolide B, a specific platelet-activating factor receptor antagonist, reduces neuronal cell apoptosis after traumatic brain injury in rats, possibly via inhibition of TLR4 signaling pathways [105]. Progesterone treatment inhibits TLR4 signaling pathways and reduces brain edema and blood–brain barrier impairment after subarachnoid hemorrhage in rats [106].…”
Section: Introductionmentioning
confidence: 99%
“…For example, oxymatrine, which has anti-inflammatory, antioxidative, and antiapoptotic activities, suppresses TLR4 and NF-κB gene expression and decreases production of proinflammatory cytokines, such as IL-6, TNF-α, and IL-1β [104]. Ginkgolide B, a specific platelet-activating factor receptor antagonist, reduces neuronal cell apoptosis after traumatic brain injury in rats, possibly via inhibition of TLR4 signaling pathways [105]. Progesterone treatment inhibits TLR4 signaling pathways and reduces brain edema and blood–brain barrier impairment after subarachnoid hemorrhage in rats [106].…”
Section: Introductionmentioning
confidence: 99%
“…TBI is the deadliest and most disabling form of acute brain trauma, accompanied by inflammatory responses and neuron apoptosis 35 . Unfortunately, there is no effective treatment for TBI so far.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of potent lipid mediated receptor inhibitors, including BN52021 and WEB2086, have been characterized2029 and shown to have therapeutic potential in a number of neurological disorders, including models of ischemia-reperfusion injury30, neuroinflammatory disease31, neurotoxic injury32. PAFR inhibitors display neuroprotective properties after TBI33343536 and these compounds might exert their effects via an inhibitory mechanism involving the interaction between PAF and PAFR3738. Our studies have demonstrated that PAFR inhibitors caused a reduction in PAF release resulting in a down regualtion of TBI induced inflammatory cytokines394041 in animal models of brain injury.…”
Section: Discussionmentioning
confidence: 99%